Permainan Bisik Berantai Terhadap Kemampuan Menyimak Arab Siswa Kelas X Excellent A di MA Al-Amien 1 Pragaan - Luthfatul Qibtiyah; Ella Rosalinda (Institut Agama Islam Negeri Metro, 2021)
This study aims to determine the effect of insya’ material on the writing skills of class x excellent students at MA Al-Amien Pragaan. This study uses a quantitative research method which consists of two variables, namely Insya' material (variable X) and writing ability (variable Y). And the data collection technique is by distributing questionnaires for variables X and Y, and observation as a support for the questionnaire, and documentation. While the subjects of this study were taken from 32 respondents. Data analysis used is the critical price table r and calculated using the SPSS formula with the formula Ŷ = a + bX. From the results of data analysis, using the linear regression formula, it can be seen that the value of the output can be determined that the value of F count = 4.304 with a significance level of 0.046 <0.05., it can be seen that there is a significant influence between the insya 'material variable (X) on the writing ability variable (Y).